Mathematical Model of Resonance Converter - Sakalauskas, S. (Elektronika ir Elektrotechnika, 2000)
There is presented mathematical model with variable structure of series-loaded resonant dc-dc power converter. The working frequency of the converter is higher than tank resonant frequency (ZVS resonant converter). By aids of the modelling there were modelled few resonant converters dedicated for solid state lasers pumping systems for continuous-wave arc lamps power supplies with intermediary DC circuit. In some cases after comparison of results of mathematical and physical modelling tests hypothesis of adequacy of models was rejected. After additional research of physical modelling there were determined four main factors not evaluated in the mathematical model. These factors become a main cause of system errors.